Efektivitas Akupresur Titik LI-4 Terhadap Nyeri Kanulasi AV-Fistula pada Pasien Chronic Kidney Disease di Unit Hemodialisis - Aryandi, Syahrul; Septiawan, Taufik; Masnina, Rusni; Rahman Hidayat, Faried; Milkhatun, Milkhatun (Pustaka Galeri Mandiri, 2026)
The kidneys are a pair of vital organs roughly the size of a fist and account for 1% of the total human body weight. Chronic kidney disease (CKD) is a medical condition in which kidney function progressively declines, resulting in the body’s inability to perform metabolism efficiently. One of the treatments for chronic kidney disease is hemodialysis, which aims to address the temporary or permanent loss of kidney function. The process requires vascular access to circulate blood, typically through the insertion of a needle into an arteriovenous fistula. This procedure causes a pain response that can lead to anxiety and fear during hemodialysis. This study discusses a case analysis regarding the management of CKD patients using acupressure at the LI-4 point to reduce pain intensity during the AV fistula cannulation process in the Hemodialysis Unit at Parikesit Tenggarong Regional General Hospital. The innovative intervention involved applying acupressure at the LI-4 point to alleviate pain for 2–3 minutes prior to and immediately before the AV fistula puncture. The study results showed a significant difference in patients’ pain scores after the acupressure intervention was applied. On the first day, the pain score decreased from 5 to 2; on the second day, from 4 to 2; and on the third day, from 4 to 1. The use of acupressure at the LI-4 point effectively reduced the intensity of pain experienced by patients during the AV fistula needle insertion process